2010
DOI: 10.2503/hrj.9.39
|View full text |Cite
|
Sign up to set email alerts
|

Application of Controlled-release Fertilizer to Forcing Culture of Tomato Using Root-proof Capillary Wick

Abstract: Root-proof capillary wick culture is expected to eliminate water drainage. Application of controlled release fertilizer instead of liquid fertilizer may be economical because liquid fertilizer equipment would not be required. In this experiment, large-fruited tomato was grown at three fertilizer levels; 11.3 gN (LF), 16.2 gN (MF), 21.0 gN (HF) per plant to evaluate a suitable level of controlled-release fertilizer needed for the culture of 15 trusses between October and July. For HF, the experiment was termina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
2
3
0
Order By: Relevance
“…In the CRF treatment, all the inorganic minerals were maintained near the threshold uptake level (i.e., minimum level required for a normal uptake) reported by Hosoi and Hosono (2005). These trends are in agreement with our previous results (Kinoshita et al, 2010a(Kinoshita et al, , 2010b. On the other hand, mineral concentrations in the CRF-treated xylem exudates after the harvesting of fruits from the first truss were much higher than the mineral concentrations in the substrate solution, similar to those observed for the LF treatment until the period of stem topping, as mentioned previously.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In the CRF treatment, all the inorganic minerals were maintained near the threshold uptake level (i.e., minimum level required for a normal uptake) reported by Hosoi and Hosono (2005). These trends are in agreement with our previous results (Kinoshita et al, 2010a(Kinoshita et al, , 2010b. On the other hand, mineral concentrations in the CRF-treated xylem exudates after the harvesting of fruits from the first truss were much higher than the mineral concentrations in the substrate solution, similar to those observed for the LF treatment until the period of stem topping, as mentioned previously.…”
Section: Discussionsupporting
confidence: 93%
“…Plants were supplied with CRF or LF. The nutrient composition of CRF was determined from our previous results (Kinoshita et al, 2010a(Kinoshita et al, , 2010b, and nutrient release from CRF was simulated using nutrient release simulation software (Sehi-meijin Version 2.0; JA Zen-noh, Tokyo, Japan). The nutrient components of CRF are shown in Table 1.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar researches on capillary irrigation showing enhanced water efficiency has also been reported (Masuda, 2008;Kinoshita et al, 2010;Ferrarezi and Testezlaf, 2016;Kamal et al, 2019). However, it has been observed that the upward movement of water via capillary action irreversibly accumulates salts in the soil media, and the salinity of water in the soil is not negligible unless water leaching occurs, hence proper monitoring and control of water supply to the capillary interface is achieved (Fujimaki et al, 2018).…”
Section: Introductionsupporting
confidence: 75%